Long-term trends in the prevalence of cardiovascular-kidney-metabolic syndrome in South Korea, 2011–2021: a representative longitudinal serial studyResearch in context - Yesol Yim; Jae E. Lee; Yejun Son; Soeun Kim; Hojae Lee; Sooji Lee; Wonwoo Jang; Hanseul Cho; Hayeon Lee; Kyeongmin Lee; Hyesu Jo; Jaeyu Park; et al. (The Lancet Regional Health. Western Pacific)
Summary: Background: The American Heart Association recently introduced a new framework, known as cardiovascular-kidney-metabolic (CKM) syndrome, aimed at the early prevention of cardiovascular disease. However, this syndrome has not been studied extensively outside of the United States. Thus, this study aimed to examine the long-term trends in CKM syndrome and its associated demographic features in South Korea. Methods: This nationwide, cross-sectional study analyzed data from 61,106 Korean adults aged ≥20 years using the Korea National Health and Nutrition Examination Survey from 2011 to 2021. CKM syndrome was defined using the PREVENT equations, categorizing individuals into five stages (0–4). Age-standardized prevalence rates, annual percent changes (APC), and sociodemographic disparities were analyzed using multinomial logistic regression and Joinpoint regression. Findings: Among the 61,106 participants (50.4% females [95% CI, 50.0–50.8%] and 49.6% males [95% CI, 49.2–50.0%]), stage 2 CKM syndrome was the most prevalent (43.4% [42.9–43.9]), followed by stages 1 (25.4% [25.0–25.8]), 0 (21.1% [20.7–21.6]), 3 (7.3% [7.0–7.5]), and 4 (2.8% [2.6–2.9]). From 2011 to 2021, advanced stages showed significant increases (APC for stage 4: 3.2%; 95% CI, 1.5–5.2), while stage 0 declined (APC: −1.9%; 95% CI, −3.8 to 0.0). Advanced stages were more common among vulnerable subgroups, including males, older adults, rural residents, smokers, drinkers, individuals with obesity, lower education levels, and lower household incomes. Interpretation: This is the first study to investigate the long-term prevalence of CKM syndrome based on stages at the national level in an Asian population. Our findings emphasize the urgent need for tailored public health strategies targeting metabolic risk factors, particularly in vulnerable subgroups, to prevent progression to advanced CKM stages. Funding: National Research Foundation of Korea.